Práticas avaliativas, formação e concepção de avaliação : caminhos percorridos na escola - Silva, Edna de Oliveira Souza (2019)
The present study is result of the research on assessment practices, education and teacher concept of assessment, developed in the context of the Master’s, in the Postgraduate Program in Education (PPGEdu), of UFMT/Rondonópolis-MT, in the line of research “Teacher Education and Educational Public Policies”, associated to the research group Organization of the Pedagogical Work and Education Centered in the School. The aim of this research was to investigate the assessment practices in the initial years of Primary Education, in order to analyze the mediation between the education of the teacher and the concept of assessment in the pedagogical act of two educators active in a school of the State System of the City of Rondonópolis-MT. As specific objectives, we pointed out the ones which emphasize that the conception of assessment guides the policy of the school, analyze if the themes studied in the teacher education integrate the assessment practices of the school and analyze which conception of assessment guides the pedagogical practice of the teacher. This investigation is developed in a context in which the public policies serve themselves, at least theoretically, from the educational assessments of large scale for initiatives of reform and take them as measure of educational quality in the country. The investigation elicited from the following question: How does the teacher understand the assessment practices and in what way do the actions of continued education developed in the school influence the pedagogical practice? The Research reported in this thesis was structured in the qualitative approach, by means of a case study, directed by the phenomenology-dialect method, in the Freirean perspective and in the conceptions of assessment of learning of Luckesi, for pointing out a dialogic and humanized attitude in the educational act. The participants were two teachers, one from the 4th and the other from the 5th year of Primary School, since these classes are in a moment of the educational journey of intense external assessment pressure due to the SAEB Exam and to the transition of the primary teachers to the specialists qualified in the subjects, along the year of 2019. The data was collected by means of interviews, of memorial, of observation of the educational meetings and of the classroom, which are recorded in the field diary, and analysis of the documents to triangulate the data. The data analysis was carried out based on the strands assessment practices, teacher education and concept of assessment. The results of the investigation reveal that the continued education is a space of meaningful relevance as it enables the teacher to reflect about the pedagogical act, as well as discuss the public policies; however, unfortunately, not always is the school able to meet the themes gathered with the school diagnosis, due to external demands stemming from the policy of Education of the State. The data also revealed that, besides the advances in the assessment practices in the perspective of the human education, there is the necessity of improving the comprehension of the educational work for emancipatory conceptions. The research highlighted the relevance of self-assessment, as well as the fact that the antidemocratic practices do not contribute for a perspective of liberating education, in the educational act.